High-Fidelity Simulation in Pediatric Emergency Medicine: A National Survey of Facilitator Comfort and Practice. Issue 4 (April 2015) - Lee, Jung; Cheng, Adam; Angelski, Carla; Allain, Dominic; Ali, Samina
Abstract : Objectives: High-fidelity simulation (HFS) is widely used in pediatric emergency medicine (PEM) training and a competent facilitator is vital for effective learning. This survey describes the characteristics, comfort, practices, and need of PEM physicians as HFS facilitators. Methods: A descriptive cross-sectional survey was electronically distributed to Pediatric Emergency Research Canada physician members, representing 14 academic pediatric emergency departments nationally. Results: The response rate was 66.6% (92/138); 63% (56/89) of PEM physicians taught HFS. Junior attending physicians ( P = 0.011) and those with an education focus ( P = 0.005) were more comfortable in using HFS. Sixty-eight percent (38/56) described their facilitator training as formal. Generally, facilitators felt comfortable in running simulations (weighted mean scale, 1.53 [<2 = comfortable] on a 5-point rating scale). Facilitators with formal training used verbal confidentiality agreements more frequently ( P = 0.008), spent less time running the scenario ( P < 0.05) and spent more time in debriefing ( P < 0.05) than those without formal training. Sixty-three percent (n = 56) of facilitators identified debriefing as the most stressful aspect of HFS. Their main barrier to HFS teaching was lack of protected teaching time (mean scale, 2.02 [>2 = barrier]). Seventy-six percent (35/46) of respondents desired online and printable facilitator information. Seventy percent (35/51) thought the ideal time for formal facilitator training was during fellowship. Conclusions: High-fidelity simulation is a widely used educational modality, and more attention must be paid to the needs of the facilitator in order to optimize the educational experience. Standardized facilitator training, focused particularly on effective debriefing techniques, would help improve facilitator comfort with HFS.